2023
DOI: 10.3390/foods12152893
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antibacterial and Antibiofilm Actions of Oregano (Origanum vulgare subsp. hirtum) Essential Oil against Salmonella Typhimurium and Listeria monocytogenes

Sonia Kolypetri,
Dimitra Kostoglou,
Anastasios Nikolaou
et al.

Abstract: Essential oils (EOs) are plant mixtures that are known to present strong bioactivities, including a wide antimicrobial action. Biofilms are microbial sessile structures that represent the default mode of growth of microorganisms in most environments. This study focused on the antimicrobial action of the EO extracted from one of the most representative oregano species, that is, Origanum vulgare (subsp. hirtum), against two important foodborne pathogens, Salmonella enterica (serovar Typhimurium) and Listeria mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…Among the EOs analyzed, EO from O. vulgare exhibited the highest antimicrobial activity in both E. coli and E. faecalis (MIC = 1.25 mg/mL), confirming the results of two of our previous studies [8,11]. This result is also in line with literature data in which the antimicrobial efficacy of this EO was demonstrated by the low MIC values determined not only with respect to the above bacteria but also with others such as S. aureus, Salmonella enteritidis, Salmonella Typhimurium, Listeria monocytogenes, and Bacillus subtilis [30][31][32][33][34][35][36]. Interestingly, this EO is the only one that, in the conditions we adopted, inhibits bacterial growth in P. aeruginosa.…”
Section: Discussionsupporting
confidence: 90%
“…Among the EOs analyzed, EO from O. vulgare exhibited the highest antimicrobial activity in both E. coli and E. faecalis (MIC = 1.25 mg/mL), confirming the results of two of our previous studies [8,11]. This result is also in line with literature data in which the antimicrobial efficacy of this EO was demonstrated by the low MIC values determined not only with respect to the above bacteria but also with others such as S. aureus, Salmonella enteritidis, Salmonella Typhimurium, Listeria monocytogenes, and Bacillus subtilis [30][31][32][33][34][35][36]. Interestingly, this EO is the only one that, in the conditions we adopted, inhibits bacterial growth in P. aeruginosa.…”
Section: Discussionsupporting
confidence: 90%
“…This inhibitory effect is observed even at extremely low concentrations, effectively impeding the formation of pathogenic biofilms. The present investigation demonstrated that Greek oregano possesses a robust antimicrobial efficacy comparable to, or potentially surpassing, that of oregano sourced from other countries, as previously reported [ 67 ]. In their study, Rupasinghe et al evaluated the mechanism by which carvacrol inhibits Streptococcus pyogenes biofilms [ 68 ].…”
Section: Bioactivity Of Essential Oils In Oregano Speciessupporting
confidence: 84%
“…It is frequently used as a flavoring herb, feed addition, and garden adornment, but it also serves as a medicine since it possesses antibacterial, antioxidant, and anti-inflammatory effects [ 134 , 135 ]. Oregano has a wide range of uses in food preservation due to the abundance of its active ingredients, including carvacrol and thymol, but it also has a unique bacteriostatic action on Salmonella enteritidis [ 136 ], Cronobacter sakazakii [ 137 ], Escherichia coli [ 135 , 138 , 139 ], Staphylococcus aureus [ 135 ], and Listeria monocytogenes [ 140 , 141 ]. There are differences in the quantity and quality of oregano essential oil (OEO) from diverse germplasm sources.…”
Section: Discussionmentioning
confidence: 99%